N-atom Density in High Ar-N2 Gas Pressure Microwave Afterglow - A. Ricard; J. Amorim (Plasmas Afterglows with \(N_2\) for Surface Treatments- Edition 2, 2022)
The determination of -atoms density in high pressure Ar- microwave afterglow is revisited. First, it is observed that pure pink afterglows are mainly obtained at high pressures up to atmospheric gas pressure, that is an factor of recombination near 0. Second, there is an uncertainty in the k-rate coefficient of the reaction which dominates the pink afterglow in the range . An enhancement of the density ratio is observed up to the atmospheric gas pressure. It was interpreted by a reduction of the quenching of the by Ar. Values of the recombination rates were determined when . It was found that they increased by about 3 from pure to contrary to the case of pure late afterglow at low gas pressure ( 8 Torr) where they decreased by about the same factor.